2020
DOI: 10.1038/s41422-020-0291-z
|View full text |Cite
|
Sign up to set email alerts
|

Targeting immunometabolism as an anti-inflammatory strategy

Abstract: The growing field of immunometabolism has taught us how metabolic cellular reactions and processes not only provide a means to generate ATP and biosynthetic precursors, but are also a way of controlling immunity and inflammation. Metabolic reprogramming of immune cells is essential for both inflammatory as well as anti-inflammatory responses. Four anti-inflammatory therapies, DMF, Metformin, Methotrexate and Rapamycin all work by affecting metabolism and/or regulating or mimicking endogenous metabolites with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
254
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 340 publications
(283 citation statements)
references
References 212 publications
(222 reference statements)
8
254
0
3
Order By: Relevance
“…Chronic pathological disorders, including cardiovascular diseases (CVDs) [ 1 , 2 ], neurodegenerative diseases [ 3 , 4 ], diabetes [ 5 , 6 ], metabolic syndrome [ 7 , 8 ], and cancer [ 9 , 10 ] share an inflammatory microenvironment as a hallmark [ 11 ]. A Common feature of these complex diseases is the activation of “sterile” inflammatory pathways, in which immune cells represent relevant effectors and drivers for the onset and progression of the disease [ 12 ], due to their extreme capability to reshape their phenotype [ 13 ], to functionally [ 14 ], metabolically [ 15 , 16 ] adapting to the surrounding environment. Among these inflammatory-mediated disorders, CVDs account as the leading cause of death worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic pathological disorders, including cardiovascular diseases (CVDs) [ 1 , 2 ], neurodegenerative diseases [ 3 , 4 ], diabetes [ 5 , 6 ], metabolic syndrome [ 7 , 8 ], and cancer [ 9 , 10 ] share an inflammatory microenvironment as a hallmark [ 11 ]. A Common feature of these complex diseases is the activation of “sterile” inflammatory pathways, in which immune cells represent relevant effectors and drivers for the onset and progression of the disease [ 12 ], due to their extreme capability to reshape their phenotype [ 13 ], to functionally [ 14 ], metabolically [ 15 , 16 ] adapting to the surrounding environment. Among these inflammatory-mediated disorders, CVDs account as the leading cause of death worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing body of evidence demonstrates that activated monocytes/macrophages strictly modulate their metabolic programs to meet the demands of participation in immune responses such as cytokine production, and that metabolites play important roles in epigenetic modifications [ 38 , 39 , 40 ]. Much focus recently has been on understanding the interconnection between metabolic reprogramming and immune function for discovering important therapeutic targets in many inflammatory disorders [ 40 , 41 , 42 , 43 ]. In diabetic CKD patients, systemic metabolic failure induced by obesity, insulin resistance, and β-cell dysfunction exacerbates the progression of renal disease [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…LPS signaling in Mϕs drives a shift to aerobic glycolysis that appears to be critical for pro‐IL‐1β synthesis, as inhibiting glycolysis with 2‐deoxyglucose suppresses IL‐1β mRNA 121,122 . Further studies have identified multiple metabolites and metabolic pathways that regulate LPS induced pro‐IL‐1β production 123 . Targeting these metabolic pathways may indirectly impact NLRP3 transcriptional priming.…”
Section: Targeting Transcriptional Priming Of the Nlrp3 Inflammasomementioning
confidence: 99%